Physiological relationship between cardiorespiratory fitness and fitness for surgery: a narrative review. (February 2023) - Roxburgh, Brendon H.; Cotter, James D.; Campbell, Holly A.; Reymann, Ulla; Wilson, Luke C.; Gwynne-Jones, David; van Rij, Andre M.; Thomas, Kate N.
Summary: Epidemiological evidence has highlighted a strong relationship between cardiorespiratory fitness and surgical outcomes; specifically, fitter patients possess heightened resilience to withstand the surgical stress response. This narrative review draws on exercise and surgical physiology research to discuss and hypothesise the potential mechanisms by which higher fitness affords perioperative benefit. A higher fitness, as indicated by higher peak rate of oxygen consumption and ability to sustain metabolic homeostasis (i.e. higher anaerobic threshold) is beneficial postoperatively when metabolic demands are increased. However, the associated adaptations with higher fitness, and the related participation in regular exercise or physical activity, might also underpin the observed perioperative benefit through a process of hormesis, a protective adaptive response to the moderate and intermittent stress of exercise. Potential mediators discussed include greater antioxidant capacity, metabolic flexibility, glycaemic control, lean body mass, and improved mood.